EZH1 Is Associated with TCP-Induced Bone Regeneration through Macrophage Polarization - Xiaoshi Jia; Hudi Xu; Richard J. Miron; Chengcheng Yin; Xiaoxin Zhang; Min Wu; Yufeng Zhang (Stem Cells International)
Macrophages have been found to regulate the effects of biomaterials throughout the entire tissue repair process as an antigen-presenting cell. As a well-defined osteoconductive biomaterial for bone defect regeneration, tricalcium phosphate (TCP) has been found to facilitate a favourable osteoimmunomodulatory response that can shift macrophage polarization towards the M2 phenotype. In the present study, our group discovered that a histone methyltransferase enhancer of zeste1 (EZH1) was drastically downregulated in Thp1 cells stimulated by TCP, indicating that EZH1 may participate in the macrophage phenotype shifting. Furthermore, the NF-κB pathway in macrophages was significantly downregulated through stimulation of TCP, suggesting a potential interaction between EZH1 and the NF-κB pathway. Utilizing gene knock-down therapy in macrophages, it was found that depletion of EZH1 induced M2 macrophage polarization but did not downregulate NF-κB. When the NF-κB pathway was inhibited, the expression of EZH1 was significantly downregulated, suggesting that the inhibition of EZH1 may be regulated by the NF-κB pathway. These novel findings provide valuable insights into a potential gene target system that controls M2 macrophage polarization which ultimately favours a microenvironment suitable for bone repair.